A személyi jövedelemadó-rendszer térbeli vonatkozásai - Kovács, Csaba (Tér és Társadalom, 1991)
In Hungary in 1988, the highly progressive system of personal income tax was elaborated with the idea, that the whole amount of the tax payable would be the income of state budget. The representatives of the parliament accepted the draft with the condition, that the tax payable after personal incomes would be due to the local councils (governments) at the permanent place of residence of the tax payers. The great regional differences of incomes liable to taxation, the immense differences in the proportion of actual tax-payers by settlements, and the highly progressive tax all together resulted in unjustifiable differences among the amounts of taxes paid by the residents of certain local governments per one tax payer and per one permanent resident, and also among their amount as compared to the incomes and expenditures of local governments. On the one hand, the author discusses and proves that with the introduction of a less progressive or linear tax system, these significant regional differences could have been avoided. On the other hand he argues, that through the redistribution of progressive income tax according to the basis of assessment or after-tax income of the settlements, the extent of the regional differences of personal income taxes due to the local councils or governments could have been decreased. The author also proves that the above methods of reditsribution might substitute those which were applied by the financial authorities in order to decrease the spatial differences of income-tax revenues due to the local governments.